Corneal Biomechanical Properties and Glaucoma-Related Quantitative Traits in the EPIC-Norfolk Eye Study - Khawaja, Anthony P. (The Association for Research in Vision and Ophthalmology, 2014)
PURPOSE. We examined the association of corneal hysteresis (CH) with Heidelberg retina tomograph (HRT)– and Glaucoma Detection with Variable Corneal Compensation scanning laser polarimeter (GDxVCC)–derived measures in a British population. METHODS. The EPIC-Norfolk Eye Study is nested within a multicenter cohort study—the European Prospective Investigation of Cancer. Ocular response analyzer (ORA), HRT3, and GDxVCC measurements were taken at the research clinic. Three ORA measurements were taken per eye, and the single best value used. Participants meeting predefined criteria were referred for a second examination, including Goldmann applanation tonometry (GAT) and central corneal thickness (CCT) measurement. Generalized estimating equation models were used to examine the associations of CH with HRT and GDxVCC parameters, adjusted for disc area. The GDxVCC analyses were adjusted further for typical scan score to handle atypical retardation. RESULTS. There were complete research clinic data from 5134 participants. Corneal hysteresis was associated positively with HRT rim area (P < 0.001), and GDxVCC retinal nerve fiber layer (RNFL) average thickness (P = 0.006) and modulation (P = 0.003), and associated negatively with HRT linear cup-to-disc ratio (LCDR, P < 0.001), after adjustment for Goldmann-correlated IOP and other possible confounders. In the 602 participants undergoing the second examination, CH was associated negatively with LCDR (P = 0.008) after adjustment for GAT, CCT, and other possible confounders. CONCLUSIONS. Lower CH was associated with HRT and GDxVCC parameters in a direction that is seen in glaucoma and with ageing. Further research is required to establish if this is a causal relationship, or due to residual confounding by age, IOP, or CCT.